Blade Serial Number Identification Based on Blade Tip Clearance without OPR Sensor. (29th December 2021) - Zhang, Liang; Wang, Qidi; Yuan, Huiqun; Li, Xin
Abstract : Blade serial number identification is one of the key issues in blade tip-timing vibration measurement without once-per-revolution (OPR) sensor. In order to overcome the shortcomings of the existing blade serial number identification methods without OPR sensor, a new identification method of blade serial number based on blade tip clearance is proposed in this paper. The relationship between blade tip-timing data and blade serial number can be identified by the matching relationship between blade tip clearance under static state and dynamic state. According to the finite element simulation and experimental data, the accuracy of the blade serial number identification method based on blade tip clearance is verified by using the OPR sensor method. The results show that in the nonresonant rotation speed region, the method can identify the blade serial number, and the identification result is consistent with the result of the OPR sensor method. In the resonance rotation speed region, when the blade tip clearance change caused by the blade circumferential bending vibration is less than the dispersion of initial blade tip clearance, the method in this paper can accurately identify the blade serial number. Otherwise, the inference method can be used. It provides theoretical support and technical basis for the engineering application of blade tip-timing vibration measurement technology without OPR sensor.